The relationships between optimal infant feeding practices and child development and attained height at age 2 years and 6–7 years - Tran, Lan Mai; Nguyen, Phuong Hong; Young, Melissa F.; Martorell, Reynaldo; Ramakrishnan, Usha (Wiley, 2024)
Limited evidence exists on the long-term effects of early feeding practices on child growth and development. We examined the relationships between infant feeding practices and child height and development at ages 2 and 6–7 years. We studied 885 mother–child dyads from a randomized controlled trial of preconception supplementation in Vietnam. Early initiation of breastfeeding (EIBF), exclusive breastfeeding (EBF), breastfeeding (BF) duration and minimum dietary diversity (MDD) were assessed using World Health Organization (WHO) guidelines. Child development was assessed by the Bayley Scales of Infant Development-III at 2 years and the Wechsler Intelligence Scale for Children® – IV at 6–7 years. Child height-for-age z-score (HAZ) was calculated from child height and age. Multivariable regression and structural equation models were used in analyses that controlled for confounding. EIBF and EBF at 6 months occurred in 52% and 62% of children, respectively. Mean breastfeeding duration was 18 months and 83% achieved MDD at 1 year. EIBF was associated with motor (β = 0.13, 95% confidence interval [CI]: 0.00, 0.28) and cognitive development at 2 years (β = 0.12, 95% CI: −0.01, 0.26), which in turn were positively associated with cognitive development at 6–7 years. EBF was directly associated with development at 6–7 years (β = 0.21, 95% CI:0.08, 0.34) whereas motor and cognitive development at 2 years explained 41%–75% of the relationship between EIBF and development at 6–7 years. HAZ at 2 years also mediated 70% of the association between MDD at 1 year and HAZ at 6–7 years. BF duration was not associated with child development and HAZ. Early infant feeding practices, especially EIBF and EBF, have important long-term implications for optimizing child linear growth and cognition as they begin school.